Parameter Identification Problem for the Kirchhoff-Type Equation with Viscosity - Jinsoo Hwang (Abstract and Applied Analysis)
The constant parameter identification problem in the Kirchhoff-type equation with viscosity is studied. The problem is formulated by a minimization of quadratic cost functionals by distributive measurements. The existence of optimal parameters and necessary optimality conditions for the parameters are proved.